CULTURAL IDENTITY OF THE FIRST GENERATION AMERICANS: A QUALITATIVE STUDY (INMR - Innovation & Management Review, 2006)
This research explores how meanings drawn from advertising and the mass media may contribute to the cultural identity of young adults who are first generation Americans and children of immigrants. We examine the meanings informants derive about U.S. culture and people, how they interpret the media portrayals of people of different national ancestries, and how such meaning-making affects their daily lives and cultural identity. A key finding is that informants experience a number of conflicts that stem from negotiating multiple and sometimes contradictory cultural messages received from the media, society, family, and friends. We explore the nature of these tensions and the role of the mass media in contributing to them. Moreover, we examine a variety of cultural identity management strategies employed by informants in dealing with these diverse influences. We close by discussing implications for advertising and media managers and avenues for future research.